THE EFFECT OF MARKETING STRATEGY AND THE USE OF THE MYPERTAMINA APPLICATION ON PERTAMAX FUEL PURCHASE DECISIONS THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Elisabeth Simatupang; Robert Tua Siregar; Cut Fitri Rostina (JURNAL PROFIT, 2026)
This study analyzes the effects of marketing strategy and the ease of use of the MyPertamina application on purchasing decisions for Pertamax, with customer satisfaction as a mediating variable in Medan City. A quantitative approach was employed using SEM-PLS with a sample of 100 MyPertamina users. The results indicate that marketing strategy has a positive and significant effect on customer satisfaction and on purchasing decisions. The ease of use of the application has a positive and significant effect on customer satisfaction, but it does not directly affect purchasing decisions. Customer satisfaction has a positive and significant effect on purchasing decisions and mediates the effects of marketing strategy and ease of use on purchasing decisions. These findings emphasize that improving purchasing decisions is more effectively achieved by strengthening customer satisfaction, both through marketing strategies and by enhancing the application’s ease of use. Practically, PT Pertamina should optimize its digital marketing and develop a MyPertamina application that is simple, reliable, and user-experience oriented to encourage Pertamax purchases.